Design, construction and study of a hybrid solar food processor in the climate of Costa Rica - Nandwani, Shyam S. (2007)
During the last 25 years, the author has designed, constructed, studied and promoted solar oven, hybrid solar/electric oven, solar oven cum drier, solar cooker cum water heater and solar still. In different parts of the world, solar cookers have been made, studied, patented, however, their real uses are very limited due to many reasons—unstable climate, economic, cultural, social and single use, etc. In order to overcome part of the problems mainly the last one, author has recently designed one hybrid food processor (multi-purposes device) and studied various technical and practical aspects. It has been used for cooking, heating/pasteurizing water (to inactivate microbes) and distillation of small quantity of water (to remove different minerals) and drying domestic products (fruits, vegetables and condiments/herbs, etc.). For more than three years of use, author has found this to be a useful device, mainly from convenience, fuel saving, economic and also from ecological point of view. This device can be used at any time and for different uses but with the reduced consumption of conventional fuel. r 2006 Elsevier Ltd. All rights reserved